P53 regulates ERK1/2/CREB cascade via a novel SASH1/MAP2K2 crosstalk to induce hyperpigmentation. Issue 10 (6th April 2017) - Zhou, Ding'an; Kuang, Zhongshu; Zeng, Xing; Wang, Ke; Ma, Jiangshu; Luo, Huangchao; Chen, Mei; Li, Yan; Zeng, Jiawei; Li, Shu; Luan, Fujun; He, Yong; et al.
Abstract: We previously reported that three point mutations in SASH1 and mutated SASH1 promote melanocyte migration in dyschromatosis universalis hereditaria (DUH) and a novel p53/POMC/Gαs/SASH1 autoregulatory positive feedback loop is regulated by SASH1 mutations to induce pathological hyperpigmentation phenotype. However, the underlying mechanism of molecular regulation to cause this hyperpigmentation disorder still remains unclear. In this study, we aimed to investigate the molecular mechanism undergirding hyperpigmentation in the dyschromatosis disorder. Our results revealed that SASH1 binds with MAP2K2 and is induced by p53‐POMC‐MC1R signal cascade to enhance the phosphorylation level of ERK1/2 and CREB. Moreover, increase in phosphorylated ERK1/2 and CREB levels and melanogenesis‐specific molecules is induced by mutated SASH1 alleles. Together, our results suggest that a novel SASH1/MAP2K2 crosstalk connects ERK1/2/CREB cascade with p53‐POMC‐MC1R cascade to cause hyperpigmentation phenotype of DUH.